Exploring the impact of resident proximity to wildfires in the northern Rocky Mountains: Perceptions of climate change risks, drought, and policy. (April 2020) - Craig, Christopher A.; Allen, Myria W.; Feng, Song; Spialek, Matthew L.
Abstract: Wildfire disaster risks are being heighted globally due to climate change. Here, we present a United States-based wildfire case study of the northern Rocky Mountains to investigate links between wildfire experience, knowledge, and perceived risk due to climate change and potential policy support for two internationally relevant strategies: land management and private/public collaboration. The 2017 fire season was one of the worst on record in the northern Rocky Mountains resulting in billions of dollars in damage and multiple casualties warranting exploration. In order to inform wildfire policy pertaining to forest land management and private/public collaboration, a survey (N = 1154) was conducted in August of 2017 among residents of 34 counties in the northern Rocky Mountains who had either experienced a close proximate large wildfire (n = 611) or had not (n = 543). Consistent with construal level theory, residents who perceived climate change is occurring had a clearer understanding of the link between climate change and local conditions (e.g., drought). Those who experienced a wildfire were more likely to support adaptive policies (i.e., land management changes, increased private/public collaboration). Residents who experienced a wildfire but did not perceive climate change risks (experienced/no risk) were less likely to attribute wildfires to drought conditions and more likely to support land management initiatives. Residents who experienced a wildfire and perceived climate change risks (experienced/risk) were more supportive of collaboration, but not land management initiatives. Theory application and implications are discussed.